2019
DOI: 10.1146/annurev-nutr-082018-124344
|View full text |Cite
|
Sign up to set email alerts
|

Bile Acids as Metabolic Regulators and Nutrient Sensors

Abstract: Bile acids facilitate nutrient absorption and are endogenous ligands for nuclear receptors that regulate lipid and energy metabolism. The brain–gut–liver axis plays an essential role in maintaining overall glucose, bile acid, and immune homeostasis. Fasting and feeding transitions alter nutrient content in the gut, which influences bile acid composition and pool size. In turn, bile acid signaling controls lipid and glucose use and protection against inflammation. Altered bile acid metabolism resulting from gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
238
1
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 270 publications
(269 citation statements)
references
References 149 publications
4
238
1
3
Order By: Relevance
“…After meal intake, bile acids are released into the gastrointestinal tract to aid in absorption of nutrients, dietary fats, steroids, vitamins, and drugs. Recent advances in basic research have identified bile acids as nutrient sensors and metabolic integrators that activate farnesoid X receptor (FXR) and Takeda G protein‐coupled receptor 5 (TGR5) to regulate lipid, glucose, and energy metabolism, and maintain metabolic homeostasis . This review will briefly cover bile acid physiology and synthesis, pathophysiology of cholestatic liver diseases and nonalcoholic fatty liver disease (NAFLD), and bile acid–based therapy for liver‐related diseases.…”
Section: Cholestatic Liver Diseasesmentioning
confidence: 99%
See 4 more Smart Citations
“…After meal intake, bile acids are released into the gastrointestinal tract to aid in absorption of nutrients, dietary fats, steroids, vitamins, and drugs. Recent advances in basic research have identified bile acids as nutrient sensors and metabolic integrators that activate farnesoid X receptor (FXR) and Takeda G protein‐coupled receptor 5 (TGR5) to regulate lipid, glucose, and energy metabolism, and maintain metabolic homeostasis . This review will briefly cover bile acid physiology and synthesis, pathophysiology of cholestatic liver diseases and nonalcoholic fatty liver disease (NAFLD), and bile acid–based therapy for liver‐related diseases.…”
Section: Cholestatic Liver Diseasesmentioning
confidence: 99%
“…Activation of TGR5 by secondary bile acids in enteroendocrine cells stimulates secretion of glucagon‐like peptide 1 (GLP‐1), which promotes insulin secretion in the pancreas to improve insulin sensitivity. TGR5 signaling also promotes adipose tissue browning and energy metabolism to reduce weight …”
Section: Cholestatic Liver Diseasesmentioning
confidence: 99%
See 3 more Smart Citations